THE EFFECT OF LEARNING MOTIVATION ON GROUP LEARNING SUCCESS AMONG STUDENTS AT POLITEKNIK LP3I JAKARTA - Salwa Alyendra; Syakila Balqis; Devina Syahrani (POLITEKNIK LP3I JAKARTA, 2026)
This research aims to investigate how motivation to learn affects the success of group-based learning among students at Politeknik LP3I Jakarta. Specifically, the study seeks to determine the level of initiative and persistence students demonstrate when working in groups, as well as how strongly their motivation enables them to cope with challenges such as imbalanced workload distribution among members. A quantitative, descriptive research design was applied in this study. Data collection was carried out through an online Likert-scale survey administered to 32 currently enrolled students at Politeknik LP3I Jakarta from the 2024–2025 cohort, selected through a stratified random sampling procedure. Using SPSS, the collected data were processed through validity and reliability testing, classical assumption testing, and simple linear regression analysis. Findings indicate that every item in the questionnaire met the criteria for validity and reliability, with a Cronbach's Alpha score of 0.870. Based on the regression analysis, the resulting equation was Y = 13.401 + 0.795X, with an R² of 0.645, indicating that 64.5% of the variance in group task productivity is explained by learning motivation. Furthermore, the partial t-test revealed a statistically significant relationship (t-count = 7.132, exceeding the t-table value of 2.042; significance level = 0.000). These findings support the conclusion that learning motivation exerts a positive and significant influence on enhancing group learning outcomes among students at Politeknik LP3I Jakarta.